Improving technical fitness of race walkers on the basis of special exercises to focus on key parameters of movements - Vinogradova, O. A.; Sovenko, S. P. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2020)
In race walking, the reliability of competitive activity, the risks of disqualification are determined by athlete's stable control of the key motion characteristics at a distance, especially in the face of fatigue. Therefore, the formation of specialized sensations in an athlete to control these movements is an important condition for sports technique improvement. Hypothesis of study: the use of special exercises to increase the analytical perception of motion key parameters will increase the effectiveness of race walking technique, control for fatigue development. Objective of study: to show the possibilities of increasing special fitness in race walking through the use of special exercises, improvement of the analytical perception of motion key parameters. Subjects and methods of study: 10 athletes aged 17-20 years and engaged in sports training for 4-6 years participated in the study. Special exercises, assessment of race walking technique (video shooting) before and after their performance within three weeks (10 sessions) were used. Results: it is shown that the targeted use of special exercises with the analysis of subjective sensations creates conditions for the activation in the athlete of specialized perceptions for the basic sports technique elements. After the use of special exercises, the increase in speed was due to an increase in the stride length - 1.14 m (S = 0.04), relative to the initial one - 1.09 m (S = 0.03) (p < 0.01). The stride length increase in athletes occurred at the expense of the length of the "rear" stride ( = 0.43 ?; S = 0.02) at statistically significant differences from the initial indices. This created the prerequisites for improving athletic performance. Conclusions. Special exercises focusing on key parameters of movements contribute to increase of technical fitness of race walkers. The proposed approach creates the prerequisites for further research on the formation of the motor composition of the skill of body position accuracy, the development of sensations of free movement, inertia, liberation from excessive degrees of freedom in the parts of the body with account for the functional state of the athlete.